šny h‛ṣym ‛šr biwk hgn - Tsevat, M.
The Two Trees in the Garden of Eden; a Tree of Death is now attested in UT 607 (published in Ugaritica V), and suggests that in Gen. 2f. the Tree of Life is original, and was balanced with the Tree of Death, also called Tree of Knowledge of Good and Bad.